Kesinambungan akidah al-Ash’ari terhadap pendekatan salaf al-salih dalam persoalan sifat - Mohd Haidhar Kamarzaman, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Imam al-Ash’ari, a prominent Muslim theologian, has contributed significantly to the development of the Sunnite creed. His approach of using reason in defending Islamic theology has put a strong and solid foundation in facing the challenge of the Muslim enemies. However, many have questioned al-Ash’ari as a continuation to the Salaf’s teachings especially from those who are against the use of reason as a methodology in Islam. They have labeled him and his school of thought as deviated from the true path of the Salaf and brought about new creed, especially in the problem of Divine’s Attributes, afar from the Salaf’s creed such as the Shi’ite, Mu’tazilite and others. This research aims at studying and evaluating whether there is continuity of thought in al- Ash’ari with the thought of the Salaf in the problem of Divine Attributes. It also attempts at studying the similarities and differences in al-Ash’ari’s and the Salaf’s thoughts in the problem of Divine Attributes. In general, the research employs qualitative methods including data collection, content analysis, comparative analysis, historical-based analysis methods. The result of the study shows that there is a prominent continuation in al-Ash’ari methodology with the Salaf’s methodology in verifying the Islamic doctrines. The continuity of thought can also be found in the issues discussed by al- Ash’ari especially pertaining to Divine Attributes.